2019
DOI: 10.3102/0013189x19852102
|View full text |Cite
|
Sign up to set email alerts
|

Pell Grant Versus Income Data in Postsecondary Research

Abstract: Given growing disparities in college enrollment by household income, policymakers and researchers often are interested in understanding whether policies expand access for low-income students. In this brief, we highlight the limitations of a commonly available measure of low-income status—whether students receive a federal Pell grant—and compare it to new data on enrollment by income quintile to evaluate a recent policy effort within elite colleges aimed at expanding access. We demonstrate that Pell is a rough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…These findings indicate that de-emphasizing or eliminating test scores from admissions consideration may be one way to interrupt inequitable enrollment patterns at these institutions. Prior analyses of testoptional policies indicate they have done little to expand access (Belasco et al, 2015;Rosinger & Ford, 2019;Saboe & Terrizzi, 2019). However, the recent decision by the University of California system (and many others in the midst of the COVID-19 pandemic) to enact test-optional policies and debates over the role of test scores in graduate and professional education warrant additional analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that de-emphasizing or eliminating test scores from admissions consideration may be one way to interrupt inequitable enrollment patterns at these institutions. Prior analyses of testoptional policies indicate they have done little to expand access (Belasco et al, 2015;Rosinger & Ford, 2019;Saboe & Terrizzi, 2019). However, the recent decision by the University of California system (and many others in the midst of the COVID-19 pandemic) to enact test-optional policies and debates over the role of test scores in graduate and professional education warrant additional analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, quasi-experimental analyses of test-optional policies have shown that they have done little to expand access (Belasco et al, 2015;Rosinger & Ford, 2019;Saboe & Terrizzi, 2019). In some cases, rather than expand access, they boosted institutional selectivity through increased applications and higher SAT scores reported to rankings agencies (Belasco et al, 2015).…”
Section: Test-optional Policies and Enrollment Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer research shows that Pell status is not a reliable indicator of lower socioeconomic status as Pell Grants can be awarded to a range of income levels. In some contexts, low-income students cannot get Pell Grants while other students do (Delisle, 2017;Harwell, 2018;Rosinger & Ford, 2019). While almost all of our survey respondents shared that providing financial assistance to students is essential to inclusive study abroad practices, we do not currently know the extent to which Pell status determines who receives financial aid for study abroad.…”
Section: Future Considerationsmentioning
confidence: 91%
“…The Pell Grant program is administered by the United States Department of Education, which determines the student's Pell eligibility through their financial need. Unlike the student loan, the Pell grants doesn't have to be repaid (Davidson, 2014;Baum, 2015;Mastrorilli, 2016;Rosinger and Ford, 2019).…”
Section: Introductionmentioning
confidence: 99%